Bayesian location of the QCD critical point: A holographic perspective - Ratti Claudia; Grefa Joaquin; Hippert Mauricio; Manning T. Andrew; Noronha Jorge; Noronha-Hostler Jacquelyn; Vazquez Israel Portillo; Rougemont Romulo; Trujillo Michael (EPJ Web of Conferences)
We present a Bayesian analysis, based on holography and constrained by lattice QCD simulations, which leads to a prediction for the existence and location of the QCD critical point. We employ two different parametrizations of the functions that characterize the breaking of conformal invariance and the baryonic charge in the Einstein-Maxwell-dilaton holographic model. They lead to predictions for the critical point that overlap at one sigma. While some samples of the prior distribution do not predict a critical point, or produce critical points that cover large regions of the phase diagram, all posterior samples present a critical point at chemical potentials µBc ~550-630 MeV.